2022
DOI: 10.1155/2022/5328192
|View full text |Cite
|
Sign up to set email alerts
|

ESM1 Is a Promising Therapeutic Target and Prognostic Indicator for Esophageal Carcinogenesis/Esophageal Squamous Cell Carcinoma

Abstract: Objective. Endothelial cell-specific molecule 1 (ESM1) has been implicated as an oncogene in several types of cancer. However, the potential role of ESM1 in esophageal carcinogenesis (ESCA)/esophageal squamous cell carcinoma (ESCC) is still unclear. Methods. The expression, function, and survival data of ESM1 were observed using a bioinformatics approach. Subsequently, the expression level of ESM1 in surgical esophageal tumors and adjacent normal tissues was detected by qRT–PCR and immunofluorescence. We furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 35 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Endothelial cell-specific molecule 1 (ESM1), a secreted proteoglycan, is overexpressed in several malignant tumors and highly associated with tumor metastasis. Thus, ESM1 is regarded as a promising therapeutic target for several tumors. , Given that ESM1 was the most significant differential gene among all 1560 DEGs, we further investigated the expression level of ESM1 in six groups via a Western blot assay. Notably, the expression of ESM1 was significantly decreased after treatment with T-HCN@CuMS+L, which was consistent with the results of migration and invasion assays (Figure E).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Endothelial cell-specific molecule 1 (ESM1), a secreted proteoglycan, is overexpressed in several malignant tumors and highly associated with tumor metastasis. Thus, ESM1 is regarded as a promising therapeutic target for several tumors. , Given that ESM1 was the most significant differential gene among all 1560 DEGs, we further investigated the expression level of ESM1 in six groups via a Western blot assay. Notably, the expression of ESM1 was significantly decreased after treatment with T-HCN@CuMS+L, which was consistent with the results of migration and invasion assays (Figure E).…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, clinical investigations have observed increased ESM1 levels in secretions or serum from patients with nasopharyngeal, endometrial and ovarian carcinoma ( 18 , 19 ). In addition, elevated ESM1 expression has been observed in cancer cells, including cervical cancer, squamous cell cancer of the head and neck, esophageal cancer and hepatocellular cancer cells ( 6 , 8 , 20 , 21 ). Notably, ESM1 expression has been demonstrated to be increased in the vascular endothelial cells of prolactinoma and gastric cancer, indicating its involvement in tumor angiogenesis ( 22 , 23 ).…”
Section: Structure and Expression Of Esm1mentioning
confidence: 99%
“…As a novel marker of cancer, ESM1 has been studied extensively. Research has shown that ESM1 is involved in the process of tumor development in two ways: Firstly, it is abnormally expressed in cancer cells and participates in tumor cell proliferation, migration and invasion ( 6 , 8 , 20 , 21 ); secondly, its expression is increased in vascular endothelial cells, which is associated with the promotion of cancer angiogenesis ( 22 , 23 ). Most of these findings have been obtained from experiments using cells or animals.…”
Section: Value Of Esm1 As a Future Therapeutic Target For Cancermentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Besides, a recent study indicates that ESM1 promotes the occurrence and development of ESCA, and promotes the malignant behavior of esophageal cancer cells. 13 However, the effects of ESM1 on STAD have not been investigated.…”
Section: Introductionmentioning
confidence: 99%